Analisis Penetapan Marketing Strategy untuk Produk Funding pada PT Bank CIMB Niaga, Tbk Kantor Cabang Pontianak - Santika, Dewi (MABIS, 2011)
This research was conducted to know how PT. Bank CIMB Niaga, Tbk. Pontianak Branch marketing strategy influence its customer to purchase funding product. This research used descriptive research and the research method was survey method. The factors in this research which influence the purchasing decision were grouped into product excellent factor, interest rate factor, office and ATM network factor, service quality and quantity factor, and office comfortable factor. Data collection techniques used was interview, questioner, and bibliography study. Sampling method was purposive sampling with the respondents are those who consumed PT. Bank CIMB Niaga, Tbk. Pontianak Branch funding product for more then 5 years and still active saving. Data analysis technique used in this research was quantitative analysis technique.